The Intel microprocessors : 8086/8088, 80186/80188, 80286, 80386, 80486, Pentium, Pentium Pro processor, Pentium II, Pentium III, Pentium 4, and Core2 with 64-bit extensions : architecture, programming, and interfacing - Brey, Barry B. 4 0 16; 5 (Upper Saddle River, NJ : Pearson/Prentice Hall, 2009)
A reference guide to Intel microprocessors that offers comprehensive coverage of developments in the field of microprocessors, programming, software development, differences between system family members, the use of real and protected modes, interface memory, and other related topics.
Includes index.
Adult;Adult.
Keywords: 2 -- 0; 6; Intel 80xxx series microprocessors.;Pentium (Microprocessor);Computer interfaces. -- 20; 20; 2